Economic impact of enterotoxigenic Eschericia coli vaccine used to control piglet neonatal colibacillosis - Zainal Arifin; Supar . (Indonesian Center for Animal Research and Development (ICARD), 1995)
Neonatal diarrhoea associated with enterotoxigenic Eschericia coli (ETEC) infections in piglets is common in most piggeries. Control of this disease is difficult with antimicrobial drugs under field conditions . It is due to the high precentage of ETEC strains resistant against there drugs. Field trials of E. coli vaccine were conducted to investigate the effect of dam vaccination on the reduction of diarrhoea and mortality rates. This study was designed in a factorial completely raralomizul block design . Vaccinated and unvaccinated dams was the first factor, while the second factor was location of the piggeries (Jakarta and Bogor) . Vaccination of sows at late gestation using a local polivalent ETEC vaccine appeared to have a dramatic reduction diarrhoea rate (P <_ 0 .0004) and mortality ride (P < 0.(x1001) in piglets. The reduction diarrhoea rate amongs the vaccinated sows in both piggeries was not significantly different (P <_ 0 .2338) . But, the mortality rate of piglets was significantly different in the vaccinated sows (P <_ 0 .026) . The economic impacts using polyvalent ETEC vaccine in controlling colibacillosis are the reduction of diarrhoea and mortality rates which leads to an increase of eveaning in piglets. These will be discussed.